Health literacy in Iranian adults: A population-based survey in southeast Iran in 2022 - Mohammadreza Rajabalipour; Mohammad Ali Morowatisharifabad; Abedin Iranpour; Behzad Mohammadi (BioSocial Health Journal)
Introduction: Health literacy (HL) is a crucial determinant of social health in any country. Based on the 7th World Health Promotion Conference in Nairobi, HL has been considered a key concept in health promotion policies since 2010. This study aimed to determine the status of HL in adults (18 to 65 years old) living in southeast Iran. Methods: This was a cross-sectional study among 460 residents of southeastern Iran. Sampling was done with the multi-stage method. Data were collected using the "Health Literacy Instrument for Adults (HELIA)". One-sample t test, analysis of variance, were also used for data analysis in SPSS 25. Results: The mean score of HL was 68.10±15.16, and 55.7% of participants had adequate HL. "Understanding and comprehension ability" had the highest mean score (75.43±18.48), while "reading ability" had the lowest (65.12±20.60). All demographic variables, except for marital status, had a significant correlation with HL. Conclusion: The level of HL among more than 55% of the participants is adequate. However, programs should focus on improving "reading ability" to better health information comprehension. Also, developing an integrated tool for measuring HL status for all regions of Iran can merge data related to Iranians’ HL status.